Peningkatan Keamanan Wireless Pada Jaringan Komputer di Universitas Amikom Menggunakan Protokol IEEE802.1X - Wiratama, Ichsan; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2019)
The access point configuration used for wireless connections in Amikom is manually configured one by one. Each access point is configured using several SSIDs based on the department that will connect to the access point. The use of multiple SSIDs in one access point turned out to have a bad effect on network performance, from the test results, for access points configured with more than four SSIDs, the connection was very slow. The security standard used for connection from the user to the access point is WPA Personal, where WPA Personal can be said to be very weak because for each SSID it will use the same user and password for all users, this is often the cause of access leaks. To improve network security and make it easier for the author to do maintenance on the network, the author tries to use the IEEE 802.1X protocol that is connected with RADIUS and access point controllers so that the configuration and maintenance of wireless networks can be centralized, user administration and passwords can also be centralized server radius and also a better level of security using WPA Enterprise security in the IEEE 802.1X protocol.